Efeito do contato humano e da aprendizagem social intra-específica na imobilidade tônica em cobaias (Cavia porcellus) - Rocha, Alan Douglas de Lima (2016)
The domestication of some animal species, aiming to supply human demands took a few thousand years. This time was not sufficient to remove several defense mechanisms developed over millions of years. Thus, even living in a totally changed environment and often free of any predators, many species still preserve the essential behaviors and former defense mechanisms. These are essentially individual in all species. But many species have social mechanisms aimed at preserving the group. The IT is an innate defense response, characterized by a state of profound physical inactivity and relative unresponsiveness to the environment. This response can be triggered by a wide range of species of vertebrates and invertebrates and is also known as an animal hypnosis or play dead. The IT appears as the last resort used by trapped in extreme effort for survival and aims to reduce the likelihood of attack maintenance, since the movement of the prey stimulates continuity. Studies have shown that contact with humans can reduce IT responses in animals. The social signaling imminent danger plays an important anti-predation adaptive function in many species. In this sense, social learning is a tool used by some species to transmission of environmental information between individuals of the group, quickly and efficiently. In the case of fear responses, animals may exhibit fear or not behavior from observing the behavior of conspecifics. In our study, we evaluated the effect of human contact on the TI responses in guinea pigs. We also evaluated the effect of cohabitation (non-fearful animals with fearful animals) on their TI responses. To achieve this, we measured the TI responses induced by postural inversion and restraint in guinea pigs after different treatments. In our first experiment, we determined the effect of human contact on TI responses by establishing 3 treatment groups: no contact, handled, and tamed. In our second experiment, we addressed the effect of social learning on TI response by testing TI response in tamed and untamed animals that had cohabitated for 10 days. In the first experiment, 10 days of either handling or taming the guinea pigs did not prevent TI, but it did increase latency and decrease duration of the TI behavior in the guinea pigs. In the second experiment, the cohabitation of untamed and tamed animals reduced TI duration in the untamed guinea pigs. These data suggest that both forms of human interaction can reduce experimenter fear in guinea pigs. It therefore seems that 3 untamed guinea pigs learn not to fear the experimenter by cohabitating with tamed guinea pigs.